Penerapan Model View Controller (MVC) Dengan Framework Codeigniter Pada Sistem Informasi Booking Wisata Klangon - Asroni, Asroni (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2018)
Special Klangon is the presence of a natural viewpoint of Mount Merapi from close range and become a favorite location for the biker mountain bike rider (mountain bike / MTB). The number of visitors who come to make managers overwhelmed to serve visitors because it still uses the management system manually by using stationery and books as a medium of recording transactions every day. The booking system there is still using sms and telfon to make mistakes when logging. The research that will be done is to convert management system in Klangon Tourism Village from manual system to computerized system. With the development of software development technology in the form of framework bebasis PHP is widely used that is Codeigniter (CI). The CI framework was developed to make it easier to develop applications. The structure of the CI Framework has implemented object-oriented programming concepts and the Models-Views-Controller (MVC) approach. This research uses CI in devel-oping this application with Waterfall method. Results Making Information System Booking Klangon Tour is an online booking process that provides information about any product that is in Klangon tourism and provide tour package information and price list of the package, Users can choose existing tour packages. Finally implementation can provide the functional benefits of online ticket management. Keywords—3-6 Tour, Klangon, booking, MVC, Codeigniter